Small rectangular parasitic plane with diamond patch antenna for WLAN application - Norra Shiella, Razali; Azremi, Abdullah Al Hadi; Saidatul Norlyana, Azemi; Soh, Ping Jack; Imran Mohd, Ibrahim (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org